1994
DOI: 10.1111/j.1745-4530.1994.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT of ENZYMES ON MICROFILTRATION of APRICOT PUREE1

Abstract: In pilot plant filtration tests, using a ceramic microfilter, it was shown that pectinase was effective in increasing flux at an enzyme level as low as 75 ppm and thatflux increased with time during filtration. Cellulase was shown to inhibit flux when used alone or in combination with pectinase, even though it contributed to reducing viscosity of the puree.Both cellulase and pectinase were partially held back by the filter; usually more than half the pectinase was retained. This resulted in increased enzyme co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…23.4) tests that used a ceramic microfilter, Hart et al (1994) showed that pectinase was effective in increasing flux at an enzyme level as low as 75 ppm and that flux increased with time during filtration. Cellulase was shown to inhibit flux when used alone or in combination with pectinase, even though it contributed to reducing viscosity of the puree (Fig.…”
Section: Apricot Pureementioning
confidence: 99%
See 2 more Smart Citations
“…23.4) tests that used a ceramic microfilter, Hart et al (1994) showed that pectinase was effective in increasing flux at an enzyme level as low as 75 ppm and that flux increased with time during filtration. Cellulase was shown to inhibit flux when used alone or in combination with pectinase, even though it contributed to reducing viscosity of the puree (Fig.…”
Section: Apricot Pureementioning
confidence: 99%
“…(Source:Hart et al (1994).) Effect of selected enzymes on apricot puree viscosity (cellulase and pectinase each added at 150 ppm levels).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Esta temperatura pode ter favorecido também a ação das enzimas que ficam retidas na membrana. Além disso, à medida que o volume do retido diminui durante a microfiltração, a concentração da enzima presente pode aumentar (HART et al, 1994). Assim, a redução da viscosidade da mistura alimentada pode ter influenciado o aumento do fluxo médio de permeado ao final do processo.…”
Section: Características Físico-químicasunclassified